KEEPING PRINCIPLES OF LEXICAL-STYLISTIC COLORING IN ENGLISH TRANSLATIONS OF THE NOVEL "BYGONE DAYS" BY A. KADIRI (Scientific journal of the Fergana State University, 2023)
The aim of the article is to clarify the keeping problems of lexical-stylistic coloring in English translations of the  novel "The Days Gone By"; Analysis of the specific features of artistic translation described in scientific works on translations from Uzbek to English and determination of methods of translation of lexical units with connotative meaning; To determine the ways of re-reflecting the stylistic features of the phraseological units used in the novel "The Days Gone By" in the translated text.